تحرّي التقصف الهيدروجيني لفولاذ تسليح الخرسانة المعالج بطريقة الفسفتة بهدف الحماية من التآكل - الحسن, أحمد سليمان; حامد, حسان محيي الدين; السويداني, عارف محمد (Latakia University Journal -Engineering Sciences Series, 2019)
رغم أن أغطية الفسفتة شائعة الاستعمال في الصناعة لحماية المعادن من التآكل، إلا أنها لم تستعمل سابقاً لمعالجة فولاذ التسليح. وبما أن معالجة السطوح المعدنية تتم عادةً في أوساط حمضية، فإن تولد الهيدروجين خلال مراحل المعالجة قد يؤدي إلى ظاهرة تدعى التقصف الهيدروجيني. وتهدف هذه الدراسة إلى المقارنة بين الخواص الميكانيكية لعينات فولاذ تسليح مفسفتة في مغاطس عدة (مغطس قياسي، مغطس قياسي مع إضافات)، وعينات أخرى غير مفسفتة تركت لأغراض المقارنة. وقد أجريت دراسة المقارنة من خلال تنفيذ مجموعة من الاختبارات الميكانيكية (شد، انحناء، إعادة انحناء) على العينات السابقة. وقد أظهرت نتائج الدراسة، أن معالجة العينات في مغاطس الفسفتة المختلفة لم يكن لها أي تأثير يذكر على الخواص الميكانيكية لهذه العينات. The use of phosphate coating is well known in industry for protecting metals against corrosion, but it was never used before for treating the reinforcing steel. Hydrogen is generated during the treatment of metallic surface by acids, as in phosphating method. This generation may lead to a phenomenon called "Hydrogen Embrittlement". This paper aims at a comparative study between phosphated and non-phosphated reinforcing steel samples. Many types of phosphating paths (standard, and standard with addition) were used for this purpose. This study was conducted through mechanical tests. (tensile, bend and rebend) applied on the previous samples. The results showed that there were no variations in the mechanical properties during the phosphating process phases.